Estimating Cancer Penetrance in Carriers of BRCA2 Pathogenic Variants Using Cancer‐Specific Polygenic Scores - Brendan Prassas; Zhuqing Shi; Huy Tran; Jun Wei; Chi‐Hsiung Wang; Andrew S. Rifkin; Annabelle Ashworth; S. Lilly Zheng; Ashley J. Mulford; Alan R. Sanders; Catherine E. Pesce; Brian T. Helfand; et al. (Cancer Medicine)
ABSTRACT Introduction BRCA2 is a causal gene for hereditary breast and ovarian cancer (HBOC) syndrome. However, its association with other cancers and interplay with polygenic scores (PGS) remains unclear. Methods An observational cohort study for the diagnosis of various cancers in the UK Biobank (UKB, N = 453,541) were recruited at ages of 40–69 years Association of germline pathogenic variants (PVs) in BRCA2 and published cancer‐specific PGS with cancer risk was tested using Cox proportional hazards model. Results The median age and interquartile range (IQR) of participants at the analysis was 58.34 (50.60–63.74) years. Carriers of BRCA2 PVs (N = 1629) had a significantly increased risk for four core HBOC‐associated cancers (breast, ovarian, pancreatic, and prostate) and six additional types of cancer (lung, oral, small intestine, larynx, liver, and mesothelioma), hazard ratio (HR) > 2.37, all ps < 0.001. For eight cancers where cancer‐specific PGS is available, each PGS was significantly associated with its respective cancer risk and independent of BRCA2, HR > 1.25 for 1 unit increase in standard deviation, all ps < 0.001. For female breast and prostate cancer, a significant interaction between BRCA2 and PGS was found (HR < 0.83, p < 0.05); the effect of PGS on cancer risk was weaker in carriers than noncarriers. The probability of cancer by age 75 years (P75) for these 10 cancers increased with higher PGS deciles in both carriers and noncarriers. For several cancers, the P75 in carriers with the lowest PGS decile was lower than that of noncarriers with the highest PGS decile. Conclusions BRCA2 PVs increase risk beyond core HBOC cancers and their risks are modified by cancer‐specific PGS. These results suggest that genetic counseling of BRCA2 PV carriers may extend to cancers beyond core HBOC syndrome and incorporate cancer‐specific PGS in estimating their penetrance.